Edukasyon bilang Tagpuan ng Katwirang Lungsod at Katwirang Lalawigan - Clemente, Noel L (Archīum Ateneo, 2016)
The city-province distinction is usually construed in economic terms: the city is the center of consumption and wealth, while the province the center of production and raw materials. In this paper, I propose that we can also draw the distinction epistemologically; instead of distinguishing between city-dwellers and provincedwellers, we can talk about city-minded and province-minded people. In this perspective, we discover the crucial position of education as the paradoxical interplay of the city mentality and province mentality. After examining this “paradox of education” as witnessed in Philippine history, especially during the Spanish and American occupations, I suggest that we can resolve the paradox by developing our system of education towards a more “nationalistic education,” as per Renato Constantino.